2017
DOI: 10.1038/srep46473
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation toxicity of indoor air pollutants in Drosophila melanogaster using integrated transcriptomics and computational behavior analyses

Abstract: We conducted an inhalation toxicity test on the alternative animal model, Drosophila melanogaster, to investigate potential hazards of indoor air pollution. The inhalation toxicity of toluene and formaldehyde was investigated using comprehensive transcriptomics and computational behavior analyses. The ingenuity pathway analysis (IPA) based on microarray data suggests the involvement of pathways related to immune response, stress response, and metabolism in formaldehyde and toluene exposure based on hub molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 56 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…In this regard, the demonstration in the present study that PM2.5 contributed to the modulation of genes such as Nod-like receptor or TLR implicated in pattern recognition receptors for the identification of bacteria, viruses, and signaling in the viruses, suggests that these effects may be possibly be related to endotoxin present in the PM2.5, although this needs to be confirmed in future studies. The innate immune response has been shown to be one of the most significantly overrepresented gene ontology terms for air pollutants, as evaluated by the Drosophila model 27 . In this regard, our study showed that PM2.5 induced Nod1 expression and increased IκBα expression and IκBα phosphorylation, thereby suggesting that once the Nods or TLRs signaling pathways are activated, these molecules trigger NF-κB that leads to the activation of transcriptional responses culminating in the expression of a subset of inflammatory genes.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the demonstration in the present study that PM2.5 contributed to the modulation of genes such as Nod-like receptor or TLR implicated in pattern recognition receptors for the identification of bacteria, viruses, and signaling in the viruses, suggests that these effects may be possibly be related to endotoxin present in the PM2.5, although this needs to be confirmed in future studies. The innate immune response has been shown to be one of the most significantly overrepresented gene ontology terms for air pollutants, as evaluated by the Drosophila model 27 . In this regard, our study showed that PM2.5 induced Nod1 expression and increased IκBα expression and IκBα phosphorylation, thereby suggesting that once the Nods or TLRs signaling pathways are activated, these molecules trigger NF-κB that leads to the activation of transcriptional responses culminating in the expression of a subset of inflammatory genes.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity assays evaluated through mortality and negative geotaxis are used as toxicity indicators of natural or synthetic chemicals, because they indicate through the mortality rate and damage to the locomotor apparatus physiological changes in the test organism, considering that the behavior is integrated to the subcellular and cellular processes of these organisms [ 46 ]. In addition, some studies in the literature perform biochemical assays to demonstrate physiological changes triggered by the substances in this alternative model, for example, we can cite oxidative stress as the main condition that is associated with the toxic profile of a substance, promoting an imbalance in the oxidant and antioxidant system of these organisms [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in disorder levels affects both internal signal transduction and the outwardly observable behavior of organisms. For instance, fruit flies show erratic flying patterns when air pollution levels are high [ 28 ]. Water fleas, mussels, fish, dolphins, and whales show increasingly disordered swimming patterns when water quality deteriorates [ 29 , 30 , 31 ].…”
Section: Disorder As a Common Response Of Organisms To High Levels Of Stressmentioning
confidence: 99%